2007
DOI: 10.1021/bm070266z
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Oligoaniline-Containing Self-Assembled Monolayers for Tissue Engineering Applications

Abstract: A novel electroactive silsesquioxane precursor, N-(4-aminophenyl)-N'-(4'-(3-triethoxysilyl-propyl-ureido) phenyl-1,4-quinonenediimine) (ATQD), was successfully synthesized from the emeraldine form of amino-capped aniline trimers via a one-step coupling reaction and subsequent purification by column chromatography. The physicochemical properties of ATQD were characterized using mass spectrometry as well as by nuclear magnetic resonance and UV-vis spectroscopy. Analysis by cyclic voltammetry confirmed that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 50 publications
3
88
0
Order By: Relevance
“…Guo et al [12] synthesized the biodegradable multi-armed branched poly(L-lactides) bearing aniline trimer segments and the polymer showed good solubility and redox properties. Wei et al [13] demonstrated that an electroactive silsequioxane precursor containing aniline trimer covalently modified by using an oligopeptide could be a promising biomaterial for tissue engineering. In our previous work, electroactive polymers with good electroactivity and biodegradability such as multi-block copolymer PLAAP of polylactide (PLA), aniline pentamer (AP), and water-soluble polymer AP cross-linking chitosan (CS) were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [12] synthesized the biodegradable multi-armed branched poly(L-lactides) bearing aniline trimer segments and the polymer showed good solubility and redox properties. Wei et al [13] demonstrated that an electroactive silsequioxane precursor containing aniline trimer covalently modified by using an oligopeptide could be a promising biomaterial for tissue engineering. In our previous work, electroactive polymers with good electroactivity and biodegradability such as multi-block copolymer PLAAP of polylactide (PLA), aniline pentamer (AP), and water-soluble polymer AP cross-linking chitosan (CS) were synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…More recently Rangappa et al [76] reported that human mesenchymal stem cells, when juxtaposed and in direct (electrical) contact with human cardiac myocytes, can be reprogrammed into the cardiomyogenic lineage. Similarly, prior studies have suggested that specific differentiative cues could be tailored into artificial scaffolds to help efficiently direct stem cell fate decisions [77,78,59,7,6,79].…”
Section: Discussion and Outlookmentioning
confidence: 97%
“…Subsequently a few groups, including us, have started to reduce into practice the idea of modulating the differentiation of stem and progenitor cells using electrical currents and, hence, generating more efficiently "better" tissue-engineered constructs [59,60,6]. Given the importance of stem cells as general cell sources for tissue engineering and regenerative medicine, and specifically of electrical currents and stimulation for neural, cardiac, and musculoskeletal tissue engineering, it is astonishing that only very few groups have thus far published on optimizing stem cell differentiation by using electrical stimulation.…”
Section: Common Routes Toward Cardiac Differentiation Of Mes Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al [41] demonstrated that an electroactive silsequioxane precursor containing an aniline trimer [i.e., N-(4-aminophenyl)-N′-(4′- (3-triethoxysilyl-propyl-ureido) phenyl-1,4-quinonenediimine) (ATQD)] could be a promising biomaterial for tissue engineering. To this end, self-assembled monolayers of ATQD on glass substrates were covalently modified with an adhesive oligopeptide, cyclic Arg-Gly-Asp (RGD) (Figure 6).…”
Section: Development Of Novel Biodegradable Samples Having Aniline Unitsmentioning
confidence: 99%